KARAKTERISTIK PENGRAJIN DAN PRODUKTIVITAS KERAJINAN ROTAN DI KECAMATAN HAUR GADING KABUPATEN HULU SUNGAI UTARA PROVINSI KALIMANTAN SELATAN - Muhammad Reza Ramadhani; Arfa Agustina Rezekiah; Rina Muhayah Noor Pitri (Jurnal Sylva Scienteae, 2020)
This study aims to analyze the characteristics of rattan craftsmen, and rattan handicraft productivity in Haur Gading District, Hulu Sungai Utara Regency, South Kalimantan Province. Data retrieval technique uses observation method by conducting direct monitoring in villages that are used as research locations in Haur Gading District. The study also carried out interviews (interviews) to the woven craftsmen in the research location related to the characteristics and productivity of handicrafts in the research location. Samples of rattan craftsmen in this study were taken by purposive sampling. The village which was used as the location of the study was taken as many as 5 villages with a total of 52 respondents who were rattan craftsmen. The results of the study showed that in total 52 residents. The majority of respondents in the study (57.69%) were between 41-60 years old and the rest (42.31%) were aged 21-40 years. In terms of education, as much as 71.15% elementary school, junior high school and senior high school / high school level were only 23.08% and 5.77% respectively. Based on gender, 69.23% came from women, and the remaining 30.77% came from men. Overall, the productivity of the craftsmen in the study location is influenced by age, educational background and gender. Craftsmen aged 21-40 years with an elementary education background have high productivity, and from all of them are dominated by women. The productivity of different craftsmen is influenced by the types of handicraft products produced.Keywords: Characteristics; Rattan Crafts; Productivity